Modeling the Factors Affecting the Establishment of Knowledge Management in Iraqi Universities - Khalifeh, Ali Doleh; Shafipour Motlagh, Farhad; Rasm Younes, Raed; Saeidian, Narges (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to model the factors affecting the implementation of knowledge management in universities in Iraq. Methods and Materials: The research method, based on its objective, was descriptive, and a survey strategy was employed. The statistical population included all faculty members in educational sciences, totaling 48,985 individuals. A random sampling method was used, and based on Cochran's sample size formula, 384 participants were selected for the study. A researcher-developed questionnaire was used as the research instrument. Content validity, convergent validity, and discriminant validity were utilized to establish the questionnaire's validity. Cronbach's alpha formula was employed to determine the reliability of the questionnaire. Data analysis was conducted using factor analysis and structural modeling tests. Findings: Overall, the results indicated that the factors affecting the implementation of knowledge management in universities in Iraq included organizational structure reconstruction (factor loading 1), organizational welfare (factor loading 0.98), organizational technology (factor loading 1), organizational leadership culture (factor loading 1), organizational excellence (factor loading 1), organizational knowledge processing (factor loading 1), constraint removal (factor loading 0.99), and stakeholder quality improvement (factor loading 1.01). Additionally, the results showed that the studied model had an acceptable fit at the level of P < 0.001. Conclusion: The study concludes that implementing knowledge management in Iraqi universities requires addressing multiple strategic factors, including organizational knowledge processes, removing constraints, enhancing welfare and leadership culture, achieving organizational excellence, leveraging technology, restructuring organizational structures, and improving stakeholder service quality. Effective strategies in these areas can significantly improve knowledge management practices and foster innovation and development in higher education institutions.